A STUDY OF THE RELATIONSHIP BETWEEN SYSTEM TESTABILITY AND MODULARITY. Issue 1 (6th April 2017) - Efatmaneshnik, Mahmoud; Ryan, Michael
ABSTRACT: Modularity is one approach to design that, amongst other design attributes, facilitates testability. However, the relationship between the type of modularization and system testability is under‐researched. In this paper we present a probabilistic model of testability that enables us to study the relationships between modularity and testability. In particular, we focus on the costs and benefits associated with the particular modularizations selected for the sole purpose of system testability. We show that adopting appropriate testing architecture through careful modularization can greatly enhance efficiency and effectiveness of system testing.